Digital Marketing Content and Consumer Trust Effects on Online Culinary Purchase Behavior - Mochamad Ihsan; Donni Juni Priansa; Ati Mustikasari (Journal of Tourism Economics and Policy, 2026)
This study examines how digital marketing content and consumer trust shape online culinary purchase behavior in the context of rapid digital transformation. The research focused on consumers who search for culinary information and buy food products through social media and online food-delivery platforms, including GoFood, GrabFood, and ShopeeFood. Because the total population was unidentified, the minimum sample was estimated using Cochran's formula, while respondents were selected purposively based on prior exposure to culinary marketing content and experience purchasing culinary products through digital media. Data were collected from 176 respondents through an online questionnaire and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with IBM SPSS Statistics 29. The results show that digital marketing content has a positive and significant effect on culinary purchase behavior, and consumer trust also has a positive and significant effect. Simultaneously, both predictors explain most of the variance in purchasing behavior, indicating that content quality and trust operate as mutually reinforcing mechanisms in digital culinary transactions. These findings imply that culinary businesses should combine informative, visually appealing, and interactive content with transparent service, consistent product delivery, and responsive communication to strengthen consumer purchasing behavior in digital channels.